Cooperative defense mechanisms for detection, identification and filtering of DDoS attacks - Mosharraf Ghahfarokhi, Negar, author; Jayasumana, Anura P., advisor; Ray, Indrakshi, advisor; Pezeshki, Ali, committee member; Malaiya, Yashwant, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.